Similar behaviour, different brain patterns: age-related changes in neural signatures of ignoring - Allen, Harriet A.; Payne, Helen (Elsevier, 2012)
We measured behavioural performance and fMRI activity whilst old and young adults performed a temporal segmentation task (‘preview search’). Being able to select parts of the visual world to be attended or ignored is a critical visual skill. Both old and young adults were able to improve their performance on a difﬁcult search task when some of the distracter items were presented earlier than the remainder. Comparisons of brain activity and functional connectivity, however, suggested that the underlying mechanisms are quite different for the two age groups. Older adults' activation patterns do not correspond to those predicted by simple increased involvement of frontal regions reﬂecting higher demand with age but seem to suggest that changes in brain activation patterns propagate throughout the cortex